Keterlibatan Anak Muda dalam Politik: Menjelajahi Peran Motivasi Informasi dan Motivasi Pribadi - Azis, Hasbullah (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The growing interest of young people in political issues has emerged as a significant focus in contemporary democratic discourse, particularly within the context of the digital era. Various discussions surrounding youth political engagement continue to generate compelling debates, underscoring the importance of understanding the extent of young people's interest in politics and the factors that shape it. This study explores the relationship between political information motivation and political participation among youth, with a particular emphasis on their involvement during the 2024 presidential election. As a crucial demographic group in shaping democratic processes, young individuals increasingly turn to digital platforms—primarily social media—to access diverse political information. Drawing upon the Uses and Gratification Theory and the Self-Determination Theory, this research examines the underlying factors that motivate youth to engage in political affairs. Employing a qualitative survey method with open-ended questions, the study involved 65 university students. The analysis reveals that young people are driven to access political information on social media by a range of motivations, including surveillance (the desire to stay informed about current political events), guidance (to understand political issues), entertainment (seeking entertainment in political issues), social utility (to support peer discussions and align with social conversations). Furthermore, the study finds that youth participation in electoral processes is primarily motivated by a sense of civic responsibility and a belief in the value of their contributions as young citizens—reflecting a form of self-determined political engagement. These findings highlight the importance of recognizing motivational and self-efficacy factors in fostering active, voluntary, and meaningful youth participation within Indonesia’s democratic landscape.